2013
DOI: 10.1627/jpi.56.142
|View full text |Cite
|
Sign up to set email alerts
|

New Surfactant Extracted from <i>Zizyphus Spina-Christi</i> for Enhanced Oil Recovery: Experimental Determination of Static Adsorption Isotherm

Abstract: A fundamental chemical enhanced oil recovery (EOR) process is surfactant flooding in which the key mechanism is to reduce interfacial tension between oil and the displacing fluid and hence mobilizing the trapped oil. Surfactant loss by adsorption is one of the most important criteria that governs the economics of the surfactant flooding methods. In addition to this, detrimental effects and high price of currently used surfactants cause EOR process so expensive and unfeasible. This study is aimed to introduce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…High adsorption of saponin nonionic surfactant at high concentrations is useful in the cases in which it is favorable to alter the wettability 57) . It must be mentioned that the adsorption values obtained were consistent with previous works 58) . It is a proven fact that the amount of surfactant adsorption is a function of surface area.…”
Section: Surfactant Adsorptionsupporting
confidence: 91%
“…High adsorption of saponin nonionic surfactant at high concentrations is useful in the cases in which it is favorable to alter the wettability 57) . It must be mentioned that the adsorption values obtained were consistent with previous works 58) . It is a proven fact that the amount of surfactant adsorption is a function of surface area.…”
Section: Surfactant Adsorptionsupporting
confidence: 91%
“…Actually dynamic condition is an appropriate field relevant condition. It is important to mention that the ratio of adsorbent to adsorbate also varies for different studies [18,19]. In the present study, as flooding experiment was conducted on sand packed, the ratio was taken in this pattern.…”
Section: Polymer Adsorption and Thickness Of Adsorbed Layersmentioning
confidence: 99%
“…In this regard, Memon et al, (2017), studied a new natural surfactant found in oil deposits in Iran. The following data can be extracted from their published work: Mohsen et al, (2013) also studied Zyziphus Spina Christi obtained from a biological source by hydro distillation of wild leaves. They conducted a static adsorption test based on an outcrop of sandstone samples.…”
Section: Core Characteristicsmentioning
confidence: 99%
“…The petroleum industry is used to using conventional surfactant for tertiary oil recovery projects (Schramm L., 2009). However, recent studies have evaluated the potential of a biosurfactant, Ziziphus Christis, which is also found in oil reservoir for enhance oil recovery projects (Safian-Boldaji et al, 2013). The motivation for these studies stems from the fact that these surfactants are naturally available and can be extracted for commercial purposes.…”
Section: Introductionmentioning
confidence: 99%